The Contribution of Family Resilience towards Youth Attitude in Drug Abuses - Ikawati Ikawati (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2016)
This research to know the enfluence of family resilience towards youth attitude in drug abuses. This researh is correlational study. Research location ditermined purposively in Yogyakarta Municipality. Research subjects ditermined purposively as many 30 respondents. Research object was family resilience and youth attitude in drug abuses. Data were gathered through questionaire distribution, interview, and observation. Data were analyzed through regresive technique.The result showed that there was coorelative regresively between independent variable in family resilience physically (X1), psychically (X2), socially (X3), and spiritually (X4), towards dependent variable (Y) in youth attitude in drug abuses. It be concluded that family resilience variable physically, psychically, socially, and spiritually enfluence or contribute youth attitude in drug abuses. Based on that result, recommended that the Ministry of Social Affairs, through Directorate of Drug Abuses Victims, put foward a program to empower family resources, like physical (economic, education, knowledge), psychical, social, and spiritual resilience.